Medical Image of the Month: Hepatic Abscess Secondary to Diverticulitis Resulting in Sepsis - Reubender Randhawa MD (Southwest Journal of Pulmonary and Critical Care, 2021)
No abstract available. Article truncated after 150 words. Clinical Scenario: A 73-year-old man with a previous history of hypertension presented to the hospital with a 4-day history of malaise, myalgias, syncope, nausea, and vomiting. He denied having any fevers, chills, diarrhea, abdominal pain, or recent travel. Upon arrival to the hospital, he was found to be febrile to 103.4°F, and hypotensive with systolic blood pressures in the 80’s. His baseline documented systolic blood pressures from numerous outpatient clinics were in the 110’s. In addition, he was hypoxemic requiring 6 L/min of supplemental oxygen to maintain an adequate oxygen saturation. Physical examination was significant for alteration of his mental status. He denied any abdominal pain with palpation, and there was no rebound tenderness or guarding. His lab work was significant for a leukopenia and thrombocytopenia - new from his previous lab work in our system. A CT of the abdomen and pelvis with contrast demonstrated a multiloculated abscess in …